Bibliometric Analysis of Natural Photoprotective Agents for Sustainable Cosmetic Applications - Sri Mastuti; Indah Hartati; Farikha Maharani; Laeli Kurniasari (Universitas Wahid Hasyim, 2026)
Ultraviolet (UV) radiation is a critical environmental stressor that accelerates oxidative damage, photoaging, and elevates the risk of skin malignancies. Although conventional sunscreens remain widely used, their drawbacks—including chemical safety concerns, limited photostability, and ecological impact—have intensified the search for natural alternatives. This study conducts a bibliometric exploration of natural photoprotective agents in cosmetic science, analysing publications from 2020 to 2025 indexed in Scopus. Using VOSviewer for co‑word mapping, 66 studies were examined to reveal thematic trends and highlight emerging compounds. The analysis points to the rising significance of polyphenols alongside marine-derived resources like seaweed. These agents are increasingly recognized for their antioxidant, anti-inflammatory, UV-protective, and pigmentation-modulating properties. Keyword clustering further illustrates the interdisciplinary nature of this research, linking cosmetic applications with toxicological and natural product studies, and emphasizing the balance between efficacy and safety. Overall, the findings indicate that polyphenols are increasingly recognized as sustainable, multifunctional ingredients poised to shape the future of cosmetic formulations.